Public conceptions of justice in climate engineering: Evidence from secondary analysis of public deliberation. (November 2016) - McLaren, Duncan; Parkhill, Karen A.; Corner, Adam; Vaughan, Naomi E.; Pidgeon, Nicholas F.
Highlights: The research explores justice issues raised by participants in public deliberation. Justice concerns such as moral hazard apply to both SRM and CDR climate engineering. Public conceptions of justice around climate responses are diverse and plural. Detailed public engagement on justice should precede climate engineering decisions. Publics tend to reject climate engineering outside a coherent, fair climate policy. Abstract: Secondary analysis of transcripts of public dialogues on climate engineering indicates that justice concerns are an important but as yet under-recognised dimension influencing public reactions to these emerging techniques. This paper describes and explores justice issues raised by participants in a series of deliberative public engagement meetings. Such justice issues included the distribution of costs and benefits across space and time; the relative power and influence of beneficiaries and others; and the weakness of procedural justice measures that might protect public interests in decision making about climate engineering. We argue that publics are mobilising diverse concepts of justice, echoing both philosophical and practical sources. We conclude that a better understanding of conceptions of justice in this context could assist exploration and understanding of public perceptions of and attitudes towards climate engineering and the different technologies involved. Such detailed public engagement would appear essential if sound, well-informed and morally justifiable decisions are to be made regarding research or development of climate engineering.